Caracterização funcional da proteína MxA: estudo do seu envolvimento com a mauinaria de SUMOilação - Carvalho, Carlos Eduardo Brantis de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The human MxA protein is a member of the superfamily of GTPases dynamins. The so called Mx proteins are present in the majority of the vertebrate organisms investigated so far and contain two structural domains, named GTPase and CID-GED (stalk), besides the capabilities of homo-oligomerization and association with intracellular membranes. Moreover, the Mx proteins are strictly produced upon cell sensibilization with type I and III interferons. The vast antiviral activity against RNA and DNA viruses, including the Influenza virus and members of the bunyaviridae family, is among the functional properties of MxA. Moreover, MX1 epigenetic silencing is associated with cellular immortalization in neoplasias. Therefore, the study of MxA is of great interest as it is a key component of the Interferon-mediated pathways and cell proliferation control. Recentely, in a two-hybrid screen using a fetal brain cDNA library, it was possible to reveal that MxA interacts with proteins related to the post-translational modification process named SUMOylation and to the assemble of the nuclear bodies named PML-NBs and with proteins implicated in the control of transcription and apoptose. In this study, it was investigated the interaction between MxA and the components of the protein SUMOylation pathway. It was possible to confirm the physical interaction between MxA and Ubc9 and SUMO1, using co-immunopreciptation assay. Then, using the yeast two-hybrid system, it was possible to determine that the EIL (E67-interacting loop) region on SUMO1 interacts with the CID-GED domain of MxA without the requirement of the SIM sequences (SUMO-interacting motif) present in MxA. Moreover, it was determined that Ubc9 interacts with the GTPase domain of MxA and that MxA homo-oligomerization is important for its interaction with SUMO1 and Ubc9. Also, we were able to demonstrate for the first time that the protein MxA undergoes SUMOylation by SUMO1, SUMO2 and SUMO3. Finally, it ...

A proteína MxA humana é membro da superfamília de GTPases dinaminas. De maneira geral, as chamadas proteínas Mx estão presentes na grande maioria dos organismos vertebrados, estudados até o momento, e possuem dois domínios estruturais, chamados GTPase e CID-GED (stalk), além da capacidade de homooligomerização e associação com membranas intracelulares. Além disso, as proteínas Mx são produzidas unicamente após a sensibilização celular por interferons do tipo I e III. Entre as propriedades funcionais de MxA, destaca-se a sua vasta atividade contra diferentes vírus de RNA e DNA, incluindo o vírus influenza e membros da família dos buniavírus. Além disso, o silenciamento gênico de MxA está associado ao fenótipo de imortalização celular em uma série de neoplasias. Assim, MxA desperta o interesse por ser uma das proteínas chave nas respostas mediadas por interferons e por estar envolvida no controle da proliferação celular. Recentemente, por meio de rastreamento de duplo-híbrido, utilizando uma biblioteca de cDNA preparada a partir de cérebro fetal humano, foi possível mostrar que MxA interage com fatores envolvidos no processo de SUMOilação de proteínas e na formação de corpúsculos nucleares denominados PMLNB e com uma série de proteínas relacionadas com o controle da transcrição e apoptose. Neste estudo, foi investigada a interação entre MxA e as proteínas envolvidas nos processo de SUMOilação. Assim, foi possível confirmar a interação física entre a proteína MxA e os ligantes Ubc9 e SUMO1, por ensaios de coimunoprecipitação. A seguir, através de ensaios de duplo-híbrido, foi possível determinar que a região EIL (E67-interacting Loop) de SUMO1 e o domínio CID-GED de MxA estão envolvidos na interação entre essas proteínas e que esta interação independe de sequências SIM (SUMO-interacting motif) presentes em MxA. Ainda, foi possível determinar que Ubc9 interage diretamente com ...
Keywords: Biotecnologia; Virus da estomatite vesicular; Interferon; Anticorpos policlonais; Polyclonal